Randomized, evaluator-blinded comparative study of a potassium titanyl phosphate (KTP) 532-nm picosecond laser and an alexandrite 755-nm picosecond laser for the treatment of solar lentigines in Asians - Vasanop Vachiramon (2022)
Background: Various pigment-specific lasers can be used to treat solar lentigines. However, the most effective treatment options remain to be explored to reduce complications, such as postinflammatory hyperpigmentation, especially in dark-skinned patients. Objectives: This study aims to compare the efficacy and safety between the KTP 532-nm picosecond laser and the alexandrite 755-nm picosecond laser for the treatment of solar lentigines in Asians. Materials and Methods: Thirty patients who had at least two solar lentigines on their arms were enrolled. A total of 30 paired lentiginous lesions were randomly selected for a single treatment with either a KTP 532-nm picosecond laser or an alexandrite 755-nm picosecond laser. Mean luminance score (L*) was evaluated at baseline and at 6 and 12 weeks to determine treatment efficacy. Improvement was assessed by a blinded physician using a 5-point score. Satisfaction was rated by patients using a visual analog scale. All adverse events were documented. Results: All 30 patients completed the study. Both lasers showed significant improvement in mean L* from baseline (p < 0.001). With the parameter settings employed, lesions treated with the alexandrite 755-nm picosecond laser showed greater improvement in mean L* when compared with treatment with the KTP 532-nm picosecond laser at 12 weeks follow-up (p = 0.002). According to physician scoring, more than 50% improvement was observed in 25 and 19 lesions of the alexandrite 755-nm picosecond laser group and the KTP 532-nm picosecond laser group, respectively. Adverse events did not differ between groups. A significantly higher satisfaction score was observed with the alexandrite 755-nm picosecond laser at the last visit (p = 0.038). Conclusion: Both types of picosecond laser may be used to treat solar lentigines. Proper treatment settings and endpoint observation are the most important factor to achieve a successful outcome.